Решите уравнение, (x^2-3x-1)^2=(x^2-4x+1)^2

MrCaT2005 MrCaT2005    1   31.07.2019 00:40    0

Ответы
milk890098 milk890098  31.07.2020 23:33
Всё решение в прикреплённом файле.
 
Решите уравнение, (x^2-3x-1)^2=(x^2-4x+1)^2
ПОКАЗАТЬ ОТВЕТЫ
vladosik6448 vladosik6448  31.07.2020 23:33
(x²-3x-1)² -(x²-4x+1)² =0

(x²-3x-1 -(x²-4x+1))(x²-3x-1 +(x²-4x+1)) =0

(x²-3x-1-x²+4x-1)(x²-3x-1+x²-4x+1) =0

(x -2)(2x² -7x) =0

x(x -2)(2x -7) =0

x =0,

x -2 =0, x =2

2x -7 =0, 2x =7, x =7/2 =3.5

ответ: x =0, x =2, x =3.5
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра